The Challenges of Arabic Language Learning Based on the Merdeka Curriculum - Ghulam, Maftukh; Muflihah (LPTK UIN Syekh Wasil Kediri, 2025)
The Merdeka curriculum still leaves a number of problems in the implementative realm, especially in the learning process in the classroom. Arabic language learning at MTsN 4 Sidoarjo also faces these obstacles. This study aims to explore the challenges of implementing the Merdeka curriculum in Arabic language learning at MTsN 4 Sidoarjo. This research uses a qualitative approach with a case study type. Data were collected through interviews, observations, and documentation. Data validity checking is done through source triangulation and technique. Data were analyzed interactively with data reduction, data display, and conclusion drawing. The results showed that most Arabic teachers still have difficulties in implementing learning based on the Merdeka curriculum. The madrasah head followed up on this problem by providing training on learning methods in the Merdeka curriculum, especially regarding differentiated learning. Another effort that has been made is to complete Arabic learning infrastructure. Strict supervision of the learning activity process is also sought to improve the quality of Arabic language learning. This research has implications for a number of solutions to overcome various problems in implementing the Merdeka curriculum, especially in Arabic language learning at the secondary level.